Teacher Candidates’ Views About the Nature of Mathematics - Altun, Solmaz Damla Gedik; Yazlık, Derya Özlem (Fırat University, 2020)
The aim of this study is to examine secondary school mathematics teacher candidates’ views about the nature of mathematics. For this purpose, the research was carried out with the phenomenology model, one of the qualitative research methods. The participants of the study consist of 21 fourth grade mathematics teacher candidates. 5 of them are male and 16 are female. The data of the study was collected with a semi-structured interview form consisting of 6 open-ended questions. The data were analyzed using content analysis method by two researchers. When the findings were examined, it was seen that the participants defined mathematics as a branch of abstract concepts that generally facilitates daily life. While most of the participants argued that mathematics is a science, only 2 of them stated that it is not science according to those who accept mathematics as a tool by not declaring their own thoughts, but science according to those who accept it as a goal. The participants stated that the basis of mathematical knowledge was based more on needs, research, logic and discovery. In addition, it was seen that the participants were in the view that mathematics was accumulated and developed from needs and logical inferences. In addition, it was determined that the majority of the participants thought that mathematics was related to daily life and other disciplines. When the data obtained at the end of the study were examined in general, it was found that the participants could not give in-depth answers to the definition and nature of mathematics. For this reason, it is considered that the discussions about the nature of mathematics and the importance of mathematical thinking should be included at each classroom level in teacher training programs.

Bu araştırmanın amacı ortaokul matematik öğretmen adaylarının matematiğin doğasına ilişkin düşüncelerinin incelenmesidir. Bu amaç doğrultusunda araştırma nitel araştırma yöntemlerinden olgubilim modeli ile yürütülmüştür. Araştırmanın katılımcılarını 21 dördüncü sınıf matematik öğretmen adayı oluşturmaktadır. Bunların 5’i erkek, 16’sı ise kızdır. Araştırmanın verileri 6 açık uçlu sorudan oluşan yarı yapılandırılmış görüşme formu ile toplanmıştır. Elde edilen veriler içerik analizi yöntemi ile iki araştırmacı tarafından analiz edilmiştir. Bulgular incelendiğinde katılımcıların matematiği genellikle günlük hayatı kolaylaştıran, soyut kavramlardan oluşan bir bilim dalı olarak tanımladıkları görülmüştür. Katılımcıların çoğu matematiğin bir bilim olduğunu savunurken, sadece ikisi kendi düşüncelerini beyan etmeyerek matematiği araç olarak kabul edenlere göre bilim olmadığını, amaç olarak kabul edenlere göre de bilim olduğunu ifade etmişlerdir. Katılımcılar matematiksel bilginin temelinin daha çok ihtiyaca, araştırmaya, mantığa ve keşfe dayandığını belirtmişlerdir. Bunun yanında katılımcıların matematiğin yığılmalı, ihtiyaçlar ve mantıksal çıkarımlardan geliştiği görüşünde oldukları görülmüştür. Ayrıca katılımcıların çoğunluğunun matematiğin günlük hayat ve diğer disiplinlerle ilişkili olduğunu düşündükleri belirlenmiştir. Araştırmanın sonunda elde edilen veriler genel olarak incelendiğinde, katılımcıların matematiğin tanımına ve doğasına yönelik derinlemesine cevaplar veremedikleri tespit edilmiştir. Bu nedenle öğretmen yetiştirme programlarında matematiğin doğası ve matematiksel düşünmenin önemine dair tartışmalara her sınıf düzeyinde yer verilmesi gerektiği düşünülmektedir.
İLKÖĞRETİM MATEMATİK ÖĞRETMENİ ADAYLARININ MATEMATİĞİN DOĞASINA YÖNELİK DÜŞÜNCELERİ